2013
DOI: 10.1155/2013/682514
|View full text |Cite
|
Sign up to set email alerts
|

On the Relevance of Considering the Intermolecular Interactions on the Prediction of the Vibrational Spectra of Isopropylamine

Abstract: The effects of implicitly considering the effects of hydrogen bonding on the molecular properties, such as vibrational frequencies, were inferred on the basis of DFT calculations. Several clusters of isopropylamine were assembled and theoretically characterized. The results showed that maximum H-bond cooperativity is achieved when the amine group acts simultaneously as donor and acceptor. The effect of H-bond cooperativity manifests itself in the relative cluster stability and on the structural and vibrational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…The mPW1PW91 functional was applied, combined with the widely used 6-31G­(d) basis set, as well as with the more extensive 6-31+G­(d,p) (comprising one additional polarization function on hydrogen atoms and diffusion functions on nonhydrogen atoms), to compare the resulting activation energies. The choice of mPW1PW91, a one-parameter hybrid functional, is supported by previous works , on the validation of this theory level as an appropriate method for this kind of studies. Additionally, the more recent wB97XD functional (which includes corrections for long-range interactions and dispersion effects) was tested, yielding slightly worse results…”
Section: Methodsmentioning
confidence: 89%
“…The mPW1PW91 functional was applied, combined with the widely used 6-31G­(d) basis set, as well as with the more extensive 6-31+G­(d,p) (comprising one additional polarization function on hydrogen atoms and diffusion functions on nonhydrogen atoms), to compare the resulting activation energies. The choice of mPW1PW91, a one-parameter hybrid functional, is supported by previous works , on the validation of this theory level as an appropriate method for this kind of studies. Additionally, the more recent wB97XD functional (which includes corrections for long-range interactions and dispersion effects) was tested, yielding slightly worse results…”
Section: Methodsmentioning
confidence: 89%
“…Previous reports on the theoretical prediction of the vibrational spectra of cisdiamminedichloro-platinum (II) (cisplatin) and cisdiamminedichloro-palladium (II) [25,28] showed that the mPW1PW/6-31G* theory level yielded a good balance between the computational demands and the accuracy achieved. This theory level has also been demonstrated to be adequate for the description of hydrogen bonds involving N-H groups [24]. Despite these prior findings, the efficiency of the mPW1PW/6-31G * level was once more evaluated, within this new context, by comparison with the results obtained using a higher theory level that combines a long-range corrected hybrid functional, ωB97XD, with a much larger basis set, 6-311++G(2d,2p).…”
Section: Computational Detailsmentioning
confidence: 99%
“…Characterization of both free ligands and metal complexes has been performed by vibrational spectroscopy (Raman, Fourier transform infrared (FTIR) and inelastic neutron scattering (INS)) coupled to quantum chemical calculations [24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, the simple match between predicted and observed IR spectra may suffice. However, the interpretation of the vibrational spectra in terms of the atomic motions related to each observed signal can also provide valuable information about the chemical systems, its structure and behavior . For example, the contribution of N–H stretching motion to the different high-frequency vibrational modes of [EMIN]­[FAP] ionic pairs has shown that the hydrogen bond formed between EMIN+ and FAP– is not strong enough to explain the relatively large stability of the ion pairs .…”
Section: Introductionmentioning
confidence: 99%
“…However, the interpretation of the vibrational spectra in terms of the atomic motions related to each observed signal can also provide valuable information about the chemical systems, its structure and behavior. 22 For example, the contribution of N−H stretching motion to the different high-frequency vibrational modes of [EMIN][FAP] ionic pairs has shown that the hydrogen bond formed between EMIN+ and FAP− is not strong enough to explain the relatively large stability of the ion pairs. 8 More recently, the interpretation of predicted Raman spectra for a number of anthraquinone dyes and lakes allowed Pagliai et al not only to confirm the structure of such compounds but also to identify some signals in the experimental Raman spectra as overtones.…”
Section: Introductionmentioning
confidence: 99%